GM-CSF and IL-21-armed oncolytic vaccinia virus significantly enhances anti-tumor activity and synergizes with anti-PD1 immunotherapy in pancreatic cancer - Xuan, Yujing; Yan, Wenyi; Wang, Ruimin; Wang, Xibin; Guo, Yu; Dun, Huilin; Huan, Ziyan; Xu, Lihua; Han, Ruxia; Sun, Xianlei; Si, Lingling; Lemoine, Nicholas R.; et al. (Frontiers in Immunology, 2025)
Pancreatic cancer is one of the most aggressive cancers and poses significant challenges to current therapies because of its complex immunosuppressive tumor microenvironment (TME). Oncolytic viruses armed with immunoregulatory molecules are promising strategies to overcome limited efficacy and target inaccessible and metastatic tumors. In this study, we constructed a tumor-selective vaccinia virus (VV) with deletions of the TK and A49 genes (VVLΔTKΔA49, VVL-DD) using CRISPR-Cas9-based homologous recombination. VVL-DD exhibited significant tumor selectivity in vitro and anti-tumor potency in vivo in a murine pancreatic cancer model. Then, VVL-DD was armed with an optimal combination of immunomodulatory molecules, granulocyte-macrophage colony-stimulating factor (GM-CSF) and interleukin-21 (IL-21), to produce VVL-GL21. VVL-GL21 induced significant tumor regression after intratumoral and systemic administration. Moreover, VVL-GL21 increased the infiltration of dendritic cells (DCs), macrophages, and T cells; induced DC maturation; increased the transition from M2 to M1 macrophages; improved the formation of immune memory; prevented tumor recurrence; and effectively bolstered the immune response against tumors in multiple key immune compartments. Interestingly, mice bearing-pancreatic cancer tumors treated with VVL-GL21 showed anti-tumor immunity against lung and colon cancer tumors. Importantly, treatment with VVL-GL21 enhanced the responsiveness of tumors to the immune checkpoint inhibitor anti-PD1. Taken together, VVL-GL21 remodels the suppressive TME and has powerful anti-tumor activities as monotherapy or in combination with anti-PD1 by intratumoral or systemic delivery for the treatment of pancreatic cancer. VVL-GL21 could be used as a therapeutic cancer vaccine.